Sources of evil : studies in Mesopotamian exorcistic lore - Buylaere, Greta van.; Luukko, Mikko.; Schwemer, Daniel.; Mertens-Wagschal, Avigail. (Ancient Magic and Divination, 2018)
Sources of Evil: Studies in Mesopotamian Exorcistic Lore is a collection of thirteen essays on the body of knowledge employed by ancient Near Eastern healing experts, most prominently the 'exorcist' and the 'physician', to help patients who were suffering from misfortunes caused by divine anger, transgressions of taboos, demons, witches, or other sources of evil. The volume provides new insights into the two most important catalogues of Mesopotamian therapeutic lore, the Exorcist's Manual and the Aššur Medical Catalogue, and contains discussions of agents of evil and causes of illness, ways of repelling evil and treating patients, the interpretation of natural phenomena in the context of exorcistic lore, and a description of the symbolic cosmos with its divine and demonic inhabitants.